2015
DOI: 10.1016/j.chemosphere.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of leachate from weathering plastics: An exploratory screening study with Nitocra spinipes

Abstract: Between 60% and 80% of all marine litter is plastic. Leachate from plastics has previously been shown to cause acute toxicity in the freshwater species Daphnia magna. Here, we present an initial screening of the marine environmental hazard properties of leachates from weathering plastics to the marine harpacticoid copepod [Crustacea] Nitocra spinipes. Twenty-one plastic products made of different polymeric materials were leached and irradiated with artificial sunlight. Eight of the twenty-one plastics (38%) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
137
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(170 citation statements)
references
References 15 publications
6
137
1
7
Order By: Relevance
“…For instance, with a liquid to solid (L/S) ratio of 10 and 24 h leaching time, leachates from polyvinyl chloride (PVC), polyurethane (PUR), and polycarbonate (PC) were the most toxic with EC 50 values of 5-69 g plastic L À1 [98]. Higher L/S ratios and longer leaching times resulted in leachates from plasticised PVC and epoxy resin products to be the most toxic at (EC 50 of 2-235 g plastic L À1 ) [99]. In a recent study, Bejgarn et al [99] investigated the leachates from plastic that were ground to a power and had undergone artificial weathering, using a L/S of 10 and a 72 h leaching time, to the marine harpacticoid copepod Nitocra spinipes.…”
Section: Effects Of Leaching Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, with a liquid to solid (L/S) ratio of 10 and 24 h leaching time, leachates from polyvinyl chloride (PVC), polyurethane (PUR), and polycarbonate (PC) were the most toxic with EC 50 values of 5-69 g plastic L À1 [98]. Higher L/S ratios and longer leaching times resulted in leachates from plasticised PVC and epoxy resin products to be the most toxic at (EC 50 of 2-235 g plastic L À1 ) [99]. In a recent study, Bejgarn et al [99] investigated the leachates from plastic that were ground to a power and had undergone artificial weathering, using a L/S of 10 and a 72 h leaching time, to the marine harpacticoid copepod Nitocra spinipes.…”
Section: Effects Of Leaching Chemicalsmentioning
confidence: 99%
“…Higher L/S ratios and longer leaching times resulted in leachates from plasticised PVC and epoxy resin products to be the most toxic at (EC 50 of 2-235 g plastic L À1 ) [99]. In a recent study, Bejgarn et al [99] investigated the leachates from plastic that were ground to a power and had undergone artificial weathering, using a L/S of 10 and a 72 h leaching time, to the marine harpacticoid copepod Nitocra spinipes. Here, leachates from different PVC materials differed in their toxicity, with the toxicity of leachate from PVC packaging increasing after artificial weathering; whereas the leachate from PVC garden hose material decreased after artificial weathering [99].…”
Section: Effects Of Leaching Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute toxicity of plastic leachates has already been proposed as a useful method to differentiate between toxic and nontoxic products (Lithner et al 2009). Nevertheless, in contrast with previous approaches (Lithner et al 2009(Lithner et al , 2012Bejgarn et al 2015;Nobre et al 2015;Gandara E Silva et al 2016;Li et al 2016), the procedure described in the present study includes a particle test conducted under more environmentally relevant conditions that facilitate continuous contact in the water column between microplastics and organisms throughout the exposure period. Thus an additional avenue of exposure not considered in earlier processes-ingestion of microplastic particles-is included in this evaluation.…”
Section: Derivation Of a Standard Protocolmentioning
confidence: 99%
“…A range of plastics, such as PS (Garrigos et al 2004), PVC (Marcilla et al 2004), andPC (vom Saal andHughes 2005), have been shown to release toxic monomers, which are associated with cancer and reproductive abnormities. Although no individual chemical structures were identified in the leachates from the plastics under artificial sunlight in a broad chemical screening study, 38% of plastics have been shown to produce leachates that caused acute toxicity to Nitocra spinipes (Bejgarn et al 2015). Many of the additives are toxic.…”
Section: Microplastics As a Source Of Toxic Chemicalsmentioning
confidence: 99%